STRENGTHENING THE ENTREPRENEURIAL SPIRIT OF THE DISABLED COMMUNITY THROUGH DIGITAL MARKETING TRAINING AT MALANG REGENCY - Prasestyia, Ferry; Santoso, Dwi Budi; Wicesa, Nayaka Artha; Arifandi, Muhammad Rizky (Faculty of Administrative Science, Universitas Brawijaya, 2026)
Disability groups still receive discriminatory treatment and do not get the same opportunities as non-disabled groups in almost all aspects, especially related to employment issues. The involvement of people with disabilities in the economy is one of the Sustainable Development Goals (SDGs). Noticing the number of people with disabilities in Malang Regency, it is critical to encourage Micro, Small, and Medium Enterprises (MSMEs) with Disabilities in Malang Regency to grow. As a result, people with disabilities in the region are hesitant about being unable to promote their products due to their lack of skills. Therefore, this service aims to provide digital marketing training to people with disabilities in Malang Regency. Based on the results of the service activities, it can be concluded that the activities have been running as expected. All participants looked very enthusiastic during a series of training activities, exhibitions, and seminars. After participating in the training, participants can apply the knowledge gained, namely related to digital marketing and product photo training.